Distributed Skills in Camel Herding. Cooperation in a Human-Animal Relationship in Somaliland - Raphael Schwere (Relations, 2021)
This article examines interspecies cooperation in camel herding in Somaliland. It presents the case of a particular joint activity in this task-scape: moving a camel herd, by leading and driving it, from the night-camp to the daytime grazing area and back. The analytical aim is to clarify the role that skills and nonhuman agency play in the constitution of cooperative human-camel relationships. On the basis of empirical data, collected in a multispecies ethnographic project by following and observing one herd and herder closely, this article demonstrates how nonhuman agency, as an individual capacity to engage in an activity and an epistemological potential, manifests in this human-camel cooperative task. Cooperation is made possible through human-camel sociality and intersubjectivity, through the ability to interpret and respond to each other, and it depends on the empathetic acknowledgement of the enabling or disabling powers of each counterpart, her or his agency. Leading and driving camels is a skilled practice requiring the responding and enabling capacities of the cooperation partner. Hence, it is a case of distributed skills – distributed in the sense that skills of humans and nonhumans are intertwined in this practice, that they complement each other.